Technology Training on How to Create a Database for Sub-district Office Archives - Wahrini, Retyana; Hasbi (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2024)
The purpose of this community service activity is to provide knowledge to the community directly through training that is held. One of the training objects given to employees in Sidorejo Village, Yogyakarta. The training given is about creating and managing databases to facilitate archiving of letters in the village. A database is an information system that functions to input and process data in a computerized manner that can be used at any time by users of the system. The activity of creating a village database is carried out with a community approach, one of which is by forming village database cadres. This process is carried out using training. So that in its implementation by using a learning process such as lectures to explain the material and practice of filling in the database itself and field work that is carried out directly after the training. The implementation of this program is carried out with several things including preparation and implementation of the program. The implementation of the program begins with the formation of database cadres and then training cadres to provide knowledge and skills. The creation of a community-based database has contributed to the village government.